THE NEUTRALIZATION ON AN EMPTY NUMBER LINE MODEL FOR INTEGER ADDITIONS AND SUBTRACTIONS: IS IT HELPFUL? - Puspita Sari; Mimi Nur Hajizah; Swida Purwanto (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2020)
The number line and the neutralization model have been used very extensively in teaching integer additions and subtractions for decades. Despite their advantages, issues concerning subtractions on these models are still debatable. Therefore, the neutralization on an empty number line (NNL) model is proposed in this research to help students better understand the meaning of integer subtractions as well as additions. This report is a part of a design research study conducted in a classroom of 28 elementary school students at the fifth grade. Data were gathered by collecting students’ written work, conducting interviews and observations during the teaching experiment. This paper focuses on students’ perceptions of the NNL model and what factors that might contribute to students’ achievements in understanding integer additions and subtractions. The analysis revealed that most students overemphasized on the use of the NNL model as a procedural method instead of as a model for thinking. Moreover, students’ mathematical beliefs and conceptions on the use of the column strategy and the absence of a discussion on the need of using the model are found to be some factors that could cause students’ misunderstandings. However, with a thorough planning, the NNL model has a potential to help students developing a meaning of integer additions and subtractions.